Conductive silver paste for HJT and preparation method, use method and application thereof

By using conductive silver paste containing phenolic epoxy resin and bisphenol A epoxy resin in HJT batteries, the existing conductive silver paste has solved the problems of high resistivity and low tension and aging tension, and has achieved lower resistivity and higher welding tension and aging resistance.

CN119763894AActive Publication Date: 2025-04-04TUNGHSU TECH GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411745371.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing conductive silver paste for HJT has problems such as high resistivity, low tension and aging tension, large impact on hot and cold environment changes, and poor corrosion resistance.

Method used

A conductive silver paste including silver powder, phenolic epoxy resin, bisphenol A type epoxy resin, polyvinylidene fluoride and antioxidants is used to improve the aging performance and printing properties of the paste through specific component ratios and processes.

Benefits of technology

It significantly reduces the resistivity and contact resistivity of conductive silver paste, improves welding tension and aging resistance, reduces the impact of changes in hot and cold environments, and enhances the stability and corrosion resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to conductive silver paste for HJT and a preparation method, a use method and application of the conductive silver paste. The conductive silver paste comprises silver powder, a first organic component, a second organic component and an organic solvent, the first organic component comprises phenolic epoxy resin, bisphenol A epoxy resin, polyvinylidene fluoride and an antioxidant, and the second organic component comprises a curing agent and terminated polyurethane resin. The conductive silver paste has the advantages of being low in resistivity, high in welding tension, small in cold and hot environment change influence and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the photovoltaic field, and in particular to a conductive silver paste for HJT, a preparation method and a use method of the conductive silver paste, and an application of the conductive silver paste in the photovoltaic field. Background Art

[0002] HJT cells, the full name of which is Heterojunction with Intrinsic Thin-layer Technology, are a next-generation solar cell technology based on an n-type silicon substrate. HJT cells form a heterojunction structure by depositing an amorphous silicon thin film on crystalline silicon, thereby combining the advantages of crystalline silicon cells and thin-film cells. HJT cells have the advantages of high photoelectric conversion efficiency, low process temperature, high stability, low attenuation rate, and double-sided power generation, and are an important direction for the current development of solar cell technology.

[0003] In the production process of HJT batteries, conductive silver paste is one of the key materials, especially in the preparation of the front electrode of the battery. The conductive silver paste for the front of HJT is usually required to have low-temperature curing performance, high conductivity and good printability. Because the process temperature of HJT batteries is usually below 250°C, the conductive silver paste needs to have low-temperature curing performance to ensure good adhesion and conductivity at low temperatures; at the same time, the electrode preparation of HJT batteries usually adopts screen printing technology, which requires the conductive silver paste to have good printability to ensure the clarity and uniformity of the electrode pattern; in addition, because the conductivity of the conductive silver paste directly affects the photoelectric conversion efficiency of the battery, the silver paste is required to have higher conductivity. However, the existing conductive silver paste for HJT has problems such as high resistivity, low tensile force and aging tensile force, large impact of cold and hot environment changes, and poor corrosion resistance.

[0004] With the continuous development of HJT battery technology and the acceleration of industrialization, the performance of conductive silver paste for HJT batteries needs to be optimized and improved. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a conductive silver paste for HJT and a preparation method, a use method and an application thereof, so as to solve the problems of the existing conductive silver paste for HJT, such as high resistivity, low tensile force and aging tensile force, and great influence of cold and hot environment changes.

[0006] To achieve the above objectives, the first aspect of the present invention provides a conductive silver paste for HJT, which comprises silver powder, a first organic component, a second organic component and an organic solvent, wherein the first organic component comprises a phenolic epoxy resin, a bisphenol A epoxy resin, polyvinylidene fluoride and an antioxidant, and the second organic component comprises a curing agent and a blocked polyurethane resin.

[0007] Based on the above technical solution, preferably, the conductive silver paste for HJT has, by weight percentage, a silver powder content of 80-90 weight %, a first organic component content of 2-5 weight %, a second organic component content of 2-5 weight %, and an organic solvent content of 6-15 weight %.

[0008] Based on the above technical solution, preferably, the first organic component, by weight percentage, comprises 50-70% by weight of phenolic epoxy resin, 20-25% by weight of bisphenol A epoxy resin, 4-8% by weight of polyvinylidene fluoride, and 6-20% by weight of antioxidant.

[0009] On the basis of the above technical solution, preferably, the weight ratio of the novolac epoxy resin to the bisphenol A epoxy resin is 1:0.3-0.45.

[0010] On the basis of the above technical solution, preferably, the weight ratio of the phenolic epoxy resin to polyvinylidene fluoride is 1:0.06-0.15.

[0011] On the basis of the above technical solution, preferably, the second organic component, by weight percentage, has a curing agent content of 80-90% by weight and a blocked polyurethane resin content of 10-20% by weight.

[0012] On the basis of the above technical solution, preferably, the weight ratio of the first organic component to the second organic component is 1:0.5-1.5.

[0013] On the basis of the above technical solution, preferably, the conductive silver paste for HJT further includes additives. More preferably, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent. In the present invention, the dispersant, the leveling agent, the thixotropic agent, the coupling agent and the defoaming agent may be conventional options in the art, for example, the dispersant may be BYK-W980, etc.; the coupling agent may be a silane coupling agent, etc.; the leveling agent may be castor oil, etc.; the defoaming agent may be dimethyl silicone oil, etc. In the present invention, the additive may be added in an amount of 0.1-0.5 parts by weight based on the total weight of the conductive silver paste for HJT. For example, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, etc.

[0014] On the basis of the above technical solution, preferably, the phenolic epoxy resin is F51 phenolic epoxy resin and / or F44 phenolic epoxy resin.

[0015] On the basis of the above technical solution, preferably, the bisphenol A epoxy resin is one or more of bisphenol A epoxy resin E03, bisphenol A epoxy resin E44, and bisphenol A epoxy resin E51.

[0016] Based on the above technical solution, preferably, the antioxidant is selected from antioxidant 168 and / or antioxidant 1010.

[0017] On the basis of the above technical solution, preferably, the curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecylsuccinic anhydride.

[0018] On the basis of the above technical solution, preferably, the organic solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate.

[0019] The second aspect of the present invention provides a method for preparing the above-mentioned conductive silver paste for HJT, comprising:

[0020] Step 1. Mixing a phenolic epoxy resin, a bisphenol A epoxy resin, polyvinylidene fluoride and an antioxidant to obtain a first organic component;

[0021] Step 2. Mixing silver powder, a first organic component and an organic solvent to obtain a first raw material;

[0022] Step 3: Mix the curing agent and the blocked polyurethane resin to obtain a second raw material.

[0023] In the present invention, step 1 and step 2 have a sequence, and step 3 has no sequence with step 1 and step 2.

[0024] The third aspect of the present invention provides a method for using the above-mentioned conductive silver paste for HJT, comprising: mixing a first raw material and a second raw material, screen printing and curing;

[0025] On the basis of the above technical solution, preferably, the curing conditions include: temperature of 200-300° C. and time of 1-8 hours.

[0026] A fourth aspect of the present invention provides the application of the above-mentioned conductive silver paste for HJT in photovoltaics.

[0027] Based on the above technical solution, it is preferably applied to N-type HJT batteries.

[0028] Beneficial effects of the present invention:

[0029] (1) The present invention simultaneously uses phenolic epoxy resin and bisphenol A epoxy resin to improve the aging performance of the slurry and improve brittleness. The epoxy group functionality of phenolic epoxy resin is greater than 2, which means that a higher cross-linking density can be formed after curing, thereby improving the heat resistance and photolysis resistance of the conductive silver paste. At the same time, phenolic epoxy resin has good mechanical properties, has a long life and good stability in the photovoltaic field, and can reduce the occurrence of aging. Bisphenol A epoxy resin has good processing properties and is easy to mix and form with other materials. The cured bisphenol A epoxy resin has excellent mechanical strength and good thermal stability. In a preferred case, by mixing phenolic epoxy resin and bisphenol A epoxy resin in an appropriate proportion, the advantages of phenolic epoxy resin and bisphenol A epoxy resin can be fully utilized to make up for their respective shortcomings. The high cross-linking density and stable chemical structure of phenolic epoxy resin help to improve the aging performance of the overall material and reduce the performance degradation under harsh environments such as high temperature, humidity, and ultraviolet rays. However, phenolic epoxy resin has a certain brittleness, and the addition of bisphenol A epoxy resin can balance the brittleness problem of phenolic epoxy resin through its good processing and flexibility. The two are mixed in a specific proportion and combined with other substances in the conductive paste to further increase the photolysis resistance and aging resistance of the conductive paste, reduce brittleness and improve adhesion.

[0030] (2) The crosslinking density of epoxy resin directly affects its physical and chemical properties, including hardness, strength, heat resistance and solvent resistance. High crosslinking density usually means better mechanical properties and thermal stability, but it may also cause the material to become brittle, which is particularly evident under extreme conditions such as cold and heat shock. The present invention introduces multi-functional polyurethane segments to balance the brittleness of epoxy resin through the flexibility of the polyurethane segments while maintaining sufficient crosslinking network density. The polyurethane segments themselves have good flexibility and elasticity, and can absorb and disperse energy when the epoxy resin is impacted by external forces, thereby effectively preventing the material from cracking or breaking. This toughening effect enables the modified epoxy resin to exhibit better durability and stability in harsh environments such as cold and heat, thereby improving the overall performance of the material. DETAILED DESCRIPTION

[0031] In the following technical description, for the sake of convenience of explanation, many details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details.

[0032] The terms "first", "second", etc. in the description and claims of the disclosed embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0033] The following are examples. In the following examples and comparative examples,

[0034] Hexamethylene diisocyanate-based polyisocyanate was purchased from Wanhua Chemical;

[0035] Polytetrahydrofuran diol (number average Mn is about 2000) was purchased from outside, CAS number is 25190-06-1;

[0036] Phenolic epoxy resin F51 was purchased from outside, CAS number is 24969-06-0;

[0037] Bisphenol A epoxy resin E44 was purchased from outside, with CAS number 25085-99-8;

[0038] Polyvinylidene fluoride was purchased from outside, with a CAS number of 24937-79-9;

[0039] Hexahydrophthalate was purchased from outside, with a CAS number of 85-42-7;

[0040] Antioxidant 168 was purchased from outside, with CAS number 31570-04-4;

[0041] Diethylene glycol butyl ether acetate was purchased from outside with a CAS number of 124-17-4.

[0042] Preparation Example 1

[0043] Preparation of hydroxyl-terminated polyurethane resin:

[0044] 1000 parts by weight of dehydrated polytetrahydrofuran diol and 1 part by weight of dibutyltin dilaurate catalyst are added into the reactor, stirred and mixed, and nitrogen is introduced into the reactor for protection; the temperature is raised to 65°C, and 100 parts by weight of hexamethylene diisocyanate polyisocyanate is added, and the addition is controlled to be completed within 2 hours, and the temperature does not exceed 90°C; after the addition is completed, the internal temperature is maintained at 80-90°C for 3 hours; finally, a sample is taken, and the -NCO content is titrated by di-n-butylamine method. When the test result is 0, a hydroxyl-terminated polyurethane resin is obtained.

[0045] Example 1

[0046] Preparation of conductive silver paste for HJT:

[0047] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0048] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0049] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0050] Example 2

[0051] Preparation of conductive silver paste for HJT:

[0052] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0053] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 8.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0054] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 3 parts by weight as the second raw material.

[0055] Example 3

[0056] Preparation of conductive silver paste for HJT:

[0057] Step 1, 60 parts by weight of novolac epoxy resin F51, 20 parts by weight of bisphenol A epoxy resin E44, 5 parts by weight of polyvinylidene fluoride and 15 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0058] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0059] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0060] Example 4

[0061] Preparation of conductive silver paste for HJT:

[0062] Step 1, 55 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 4 parts by weight of polyvinylidene fluoride and 16 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0063] Step 2, 80 parts by weight of silver powder, 5 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0064] Step 3: Mix 80 parts by weight of hexahydrophthalic anhydride curing agent and 20 parts by weight of blocked polyurethane resin, and take 5 parts by weight as the second raw material.

[0065] Example 5

[0066] Preparation of conductive silver paste for HJT:

[0067] Step 1, 69 parts by weight of novolac epoxy resin F51, 21 parts by weight of bisphenol A epoxy resin E44, 4 parts by weight of polyvinylidene fluoride and 6 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0068] Step 2, 80 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0069] Step 3: Mix 90 parts by weight of hexahydrophthalic anhydride curing agent and 10 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0070] Example 6

[0071] Preparation of conductive silver paste for HJT:

[0072] Step 1, 45 parts by weight of novolac epoxy resin F51, 40 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0073] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0074] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0075] Example 7

[0076] Preparation of conductive silver paste for HJT:

[0077] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 2 parts by weight of polyvinylidene fluoride and 13 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0078] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0079] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0080] Example 8

[0081] Preparation of conductive silver paste for HJT:

[0082] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0083] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 10.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0084] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 1 part by weight as the second raw material.

[0085] Example 9

[0086] Preparation of conductive silver paste for HJT:

[0087] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0088] Step 2, mixing 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin;

[0089] Step 3: Mix 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 2 parts by weight of the second organic component obtained in step 2, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980, and roll and disperse them evenly in a three-roll mill to obtain a conductive silver paste for HJT.

[0090] Comparative Example 1

[0091] Preparation of conductive silver paste for HJT:

[0092] The method of Example 1 is followed, except that the bisphenol A epoxy resin E44 is replaced by the novolac epoxy resin F51, that is:

[0093] Step 1, 85 parts by weight of phenolic epoxy resin F51, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0094] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0095] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0096] Comparative Example 2

[0097] Preparation of conductive silver paste for HJT:

[0098] The method of Example 1 is followed, except that the phenolic epoxy resin F51 is replaced by bisphenol A epoxy resin E44, that is:

[0099] Step 1, 85 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0100] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0101] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0102] Comparative Example 3

[0103] Preparation of conductive silver paste for HJT:

[0104] The method of Example 1 is followed, except that polyvinylidene fluoride is replaced by phenolic epoxy resin F51, that is:

[0105] Step 1, 68 parts by weight of phenolic epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44 and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0106] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0107] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0108] Comparative Example 4

[0109] Preparation of conductive silver paste for HJT:

[0110] The method of Example 1 is followed, except that the blocked polyurethane resin is replaced with a hexahydrophthalic anhydride curing agent, namely:

[0111] Step 1, 60 parts by weight of novolac epoxy resin F51, 25 parts by weight of bisphenol A epoxy resin E44, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 are mixed to obtain a first organic component;

[0112] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0113] Step 3: Take 2 parts by weight of hexahydrophthalic anhydride curing agent as the second raw material.

[0114] Comparative Example 5

[0115] Preparation of conductive silver paste for HJT:

[0116] The method of Example 1 is followed, except that both the novolac epoxy resin F51 and the bisphenol A epoxy resin E44 are replaced with 2,3-epoxypropyl acrylate, that is:

[0117] Step 1, mixing 85 parts by weight of 2,3-epoxypropyl acrylate, 8 parts by weight of polyvinylidene fluoride and 7 parts by weight of antioxidant 168 to obtain a first organic component;

[0118] Step 2, 85 parts by weight of silver powder, 3 parts by weight of the first organic component obtained in step 1, 9.6 parts by weight of diethylene glycol butyl ether acetate, 0.2 parts by weight of castor oil leveling agent and 0.2 parts by weight of dispersant BYK-W980 are mixed to obtain a first raw material;

[0119] Step 3: Mix 85 parts by weight of hexahydrophthalic anhydride curing agent and 15 parts by weight of blocked polyurethane resin, and take 2 parts by weight as the second raw material.

[0120] Test Case

[0121] Performance Testing:

[0122] Test Examples 1-8 and Comparative Test Examples 1-5

[0123] The first raw material and the second raw material of Examples 1-8 and Comparative Examples 1-5 were mixed respectively, and rolled and dispersed evenly in a three-roll mill to obtain a conductive silver paste for HJT. Alternatively, the conductive silver paste for HJT of Example 9 was directly tested. The resistivity, contact resistivity, peel strength and aging properties of the electrode prepared by the conductive silver paste were tested, and the results are shown in Table 1.

[0124] Test method:

[0125] (1) Test method for resistivity: The conductive pastes of the embodiment and the comparative example are screen-printed and coated on the crystalline silicon HJT solar blue film, respectively, and vacuum dried at room temperature for 3 hours. Then, it is cured using circulating hot air at a temperature of 150°C for 30 minutes to obtain a fine-wire electrode. The resistance of the fine-wire electrode is then measured using an AEMC6240 microresistance meter, and the width and length of the fine wire are measured using a WI-5000 interferometric coaxial three-dimensional stereo microscope. The pattern specifications of the fine-wire electrode formed above are that the width of the middle line segment is 40μm, the length is 9cm, and the contact pads at the head and tail are 2mm×2mm. The line resistance is measured by four-terminal sensing between the contact pads, and the measured resistance is standardized by the grid line length and multiplied by the cross-sectional area (measured using an α step profiler) to obtain the resistivity (ρ) of the grid line. Each resistivity data set is obtained by averaging the values ​​measured on four different grid lines.

[0126] (2) Test method for contact resistivity: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on the crystalline silicon HJT solar blue film, and vacuum dried at room temperature for 3 hours. Then, the film was cured using circulating hot air at 150°C for 30 minutes to obtain a fine-line electrode. The electrode pattern consisted of 5 linear electrodes with a line width of 0.5 mm and a length of 50 mm, with a line spacing of 3 mm. Then, an AEMC 6240 microresistance meter was used to measure the resistance between line electrodes with different spacings, and the contact resistivity (R c ).

[0127] (3) Test method for peel strength: The conductive pastes of the embodiment and the comparative example are screen-printed and coated on the crystalline silicon HJT solar blue film, respectively, and vacuum dried at room temperature for 3 hours. Then, it is cured using circulating hot air at a temperature of 150°C for 30 minutes to obtain a fine wire electrode. To obtain an electrode pattern. The pattern specification of the test electrode is 5 cm long and 2 mm wide, and then a tinned copper strip with a width of 1 mm is welded to the test electrode. The substrate is fixed on the tensiometer platform to test the peel strength. The tensiometer type is NLB-100 electronic push-pull pressure gauge. The test conditions are to peel off the solder strip at an angle of 180° at a speed of 60 mm / min, and obtain the tensile force value, which is recorded every 1 second. The tension obtained is the average value of a 5 cm long electrode.

[0128] (4) Test method for aging resistance: Test the attenuation of the photoelectric conversion efficiency after 200 hot and cold cycles. Aging resistance (attenuation %) = (initial photoelectric conversion efficiency - photoelectric conversion efficiency after 200 hot and cold cycles) / initial photoelectric conversion efficiency × 100%.

[0129] Table 1

[0130]

[0131]

[0132] It can be seen from the above table that the HJT conductive silver paste prepared by the formula of the present invention can reduce resistivity and contact resistance, and improve welding tension and aging resistance. In particular, in Examples 1-5, the performance is better within the weight ratio range of the specific novolac epoxy resin to bisphenol A epoxy resin and the weight ratio range of the novolac epoxy resin to polyvinylidene fluoride of the present invention.

[0133] It can be seen from the embodiments of the present invention that the formula of the present invention can be quickly cured at 150°C for 30 minutes and has a lower resistivity after curing. Compared with the existing high temperature curing conditions of 200°C-250°C, the formula of the present invention has significant improvements and is more suitable for N-type HJT batteries.

[0134] Furthermore, it can be seen from the embodiments of the present invention that, compared with the pre-mixed embodiment 9, the formulation of the present invention is more suitable for mixing the first raw material component with the second raw material component before use, which has a better effect.

[0135] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.

[0136] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.

Claims

1. A conductive silver paste for HJT, comprising silver powder, a first organic component, a second organic component and an organic solvent, wherein: The first organic component includes novolac epoxy resin, bisphenol A epoxy resin, polyvinylidene fluoride and antioxidant, and the second organic component includes curing agent and end-capped polyurethane resin.

2. The conductive silver paste for HJT according to claim 1, characterized in that: The conductive silver paste for HJT has, by weight percentage, a silver powder content of 80-90 weight %, a first organic component content of 2-5 weight %, a second organic component content of 2-5 weight %, and an organic solvent content of 6-15 weight %.

3. The conductive silver paste for HJT according to claim 1, characterized in that: The first organic component, by weight percentage, comprises 50-70% by weight of phenolic epoxy resin, 20-25% by weight of bisphenol A epoxy resin, 4-8% by weight of polyvinylidene fluoride, and 6-20% by weight of antioxidant; and / or The weight ratio of the novolac epoxy resin to the bisphenol A epoxy resin is 1:0.3-0.45; and / or, The weight ratio of the phenolic epoxy resin to the polyvinylidene fluoride is 1:0.06-0.

15.

4. The conductive silver paste for HJT according to claim 1, characterized in that: The second organic component, by weight percentage, contains 80-90% by weight of the curing agent and 10-20% by weight of the blocked polyurethane resin.

5. The conductive silver paste for HJT according to claim 1, characterized in that: The weight ratio of the first organic component to the second organic component is 1:0.5-1.

5.

6. The conductive silver paste for HJT according to claim 1, characterized in that: The conductive silver paste for HJT further includes an additive; Preferably, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent.

7. The conductive silver paste for HJT according to claim 1, characterized in that: The phenolic epoxy resin is F51 phenolic epoxy resin and / or F44 phenolic epoxy resin; and / or, The bisphenol A epoxy resin is one or more of bisphenol A epoxy resin E03, bisphenol A epoxy resin E44, and bisphenol A epoxy resin E51; and / or, The antioxidant is selected from antioxidant 168 and / or antioxidant 1010; and / or, The curing agent is selected from one or more of phthalic anhydride, hexahydrophthalic anhydride, glutaric anhydride and dodecyl succinic anhydride; and / or The organic solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate.

8. The method for preparing the conductive silver paste for HJT according to any one of claims 1 to 7, comprising: Step 1. Mixing a phenolic epoxy resin, a bisphenol A epoxy resin, polyvinylidene fluoride and an antioxidant to obtain a first organic component; Step 2. Mixing silver powder, a first organic component and an organic solvent to obtain a first raw material; Step 3: Mix the curing agent and the blocked polyurethane resin to obtain a second raw material.

9. The method for using the conductive silver paste for HJT according to any one of claims 1 to 7, comprising: Mixing the first raw material with the second raw material and screen printing and curing; Preferably, the curing conditions include: a temperature of 200-300° C. and a time of 1-8 hours.

10. The application of the conductive silver paste for HJT according to any one of claims 1 to 7 in photovoltaics, preferably in N-type HJT cells.

Citation Information

Patent Citations

  • Epoxy paste composition including silver-coated copper nanowires having core-shell structure, and conductive film including same

    CN109906246A

  • HJT low-temperature curing silver paste with dual curing performance and preparation method of HJT low-temperature curing silver paste

    CN112837844A

  • Low-temperature curing type conductive silver paste, preparation method and application thereof

    CN117976288A

  • Anisotropic conductive composition and film

    JP1998021740A

  • Conductive film, current collector using same, battery and bipolar battery

    US20140099537A1